Wearables beyond borders: A case study of barriers to gait assessment in low-resource settings. (July 2020) - Godfrey, A.; Aranda, C.; Hussain, A.; Barreto, M.; Rocha, T.; Vitório, R.
Highlights: Wearables have use in low-resource, low- to middle-income countries. This case study addresses the pragmatic challenges to the use of wearables in a large and diverse country, Brazil. Barriers to the adoption of wearables relate to regional inequalities, knowledge and resources, and trust. Abstract: Currently, there are major EU-based projects to better utilise wearables as useful diagnostic aids/tools in clinical settings as well for deployment in the home to capture ageing processes. To date, there has been little investigation of the translation of those tools beyond the geographical regions in which they were developed and implemented. Our objective was to examine pragmatic issues and challenges in the use of wearables in a diverse, low-resource, middle-income country like Brazil. We found barriers to their understanding and adoption converge on three themes: (i) regional inequalities; (ii) knowledge and resources; and (iii) trust. Current large-scale projects should consider the scalability and implementation of their methods, given those themes, facilitating a stratified and global approach to healthy ageing.